Ken Livingstone : The Thorn in (New) Labour’s Side - Timothy Whitton (Revue LISA)
Ever since Ken Livingstone became leader of the Greater London Council (GLC) in 1981, he was a constant threat for the political integrity of the Labour Party until Mrs Thatcher decided to do away with this tier of local government in 1986. The antagonism between the outspoken Livingstone and the Labour Party came to a head during the period leading up to the first mayoral elections in London in May 2000. After a rigged primary election, Livingstone had been forced into becoming an independent candidate, but despite being excluded from the Labour Party, he managed to become the first directly elected mayor of the capital city. From his new vantage point at the head of the Greater London Authority (GLA), the “third man” of England continued to defy New Labour when he considered that central government policies did not tally with what Londoners needed. The success of the congestion charge considerably reinforced his popularity and New Labour reluctantly reintegrated him within its ranks to fight the 2004 mayoral election under its colours. Despite this move, Livingstone continued to defend the GLA’s right to develop policies in keeping with the decentralisation of power even if signs of greater cooperation with central government were obvious, especially when London was given the 2012 Olympic Games in July 2005. This new stance did not prevent him from losing the 2008 election when the Conservative candidate, Boris Johnson, became mayor of London. This article will examine the antagonism between Ken Livingstone and the Labour Party in its “old” and “new” versions. New Labour created the GLA hoping that it would be the ideal relay for its political project in the capital. Had they realised that the post of executive mayor was almost tailor made for “red” Kenneth Livingstone, they would most certainly have had second thoughts.